Apoptosis during gametogenesis in diploid and triploid turbot (Scophthalmus maximus) - Terrones, J. (Jaime); Vidal, S.; Cal, R. (Rosa); Martínez, P.; Piferrer, F. (Centro Oceanográfico de Vigo, 2023)
Apoptosis was monitored in male and female diploid and triploid turbot encompassing a full gametogenic cycle. Results indicate that apoptosis is involved in the normal regulation of spermatogenesis progression and male germ cell fate, and provide the first evidence that the differential effects of triploidy on gonadal development include the induction of apoptosis in females. 1,5280